Causes and Consequences of Drug Addiction among Male Adolescents: A Case Study in Chapainawabganj - Safayet Hossen; Bristy Khatun; Md. Sael Ali; Parosha Jaha Shatul; Md Amirul Islam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The teenage (adolescent) period of life is considered very crucial in a person’s life, as it is the time when a lot of physical as well as psychological changes occur. Drug addiction among male adolescents is one of the most concerning problems in Bangladesh. The aim of this study was to investigate the condition of drug-addicted male adolescents in Shibganj municipality, Chapinawabganj district. This research was conducted through the techniques of social surveys and used quantitative data. This study selected 50 respondents through the snowball sampling method, and the data were classified and analyzed through SPSS software. 4% of male adolescents started taking drugs at the age of 12–13, 46% of male adolescents started taking drugs at the age of 14–15, 42% started taking drugs at the age of 16–17, and the rest of the 4% started taking drugs at the age of 18–19. The male adolescents’ respondents mostly take weed, and this rate is 84%. About 30% of adolescents are involved in crime for arranging money for drugs. The most important thing was that drug addiction affected their study. 34% of male adolescents are indifferent to the study, 22% drop out, 5% study break, and 18% drop out of school because of drug addiction. Therefore, all stakeholders, including guardians, teachers, education institute authorities, law makers and law-enforcing agencies, researchers, civil society, NGO's, and the state, must come forward together to prevent drug addiction among adolescents.